The Pastoral Approach to Canon Law: A Critique of the Thought of Ladislaus Örsy, Sj (Hekima Review, 2025)
In this article, I seek to analyse the pastoral approach to Canon Law as proposed by Ladislas Örsy, S.J.2 He has been a hugely influential canonist for decades, so it is important to understand his thought as regards the pastoral approach to Canon Lawsince it has gained significant influence and popularity in the Church and its attitude to law. I will argue that Örsy seeks to replace a properly juridic approach to Canon Law with a ‘community welfare-redemptive one, and so does not base Canon Law on a substantial jurisprudential foundation, thus undermining the pastoral effectiveness of Canon Law.